A Syncretic Approach to the Role of Pathological Organizations in Violence. (23rd July 2013) - Boyle, John
Abstract : This paper considers the role of pathological organizations in violence from a syncretic perspective. It begins with a discussion of the idea of syncretism in psychotherapy that is followed by an overview of the development of the pathological organization concept. Donald Kalsched's work on the self‐care system is subsequently introduced to provide a complementary Jungian perspective on the role of trauma in the formation of pathological organizations. The remainder of the paper considers the role of pathological organizations in violence with particular reference to the work of Arthur Hyatt‐Williams on 'the murder constellation' and J. Reid Meloy's concept of the 'psychopathic personality organization'. Two brief clinical vignettes are included to illustrate selected aspects of the theoretical material. By way of conclusion the paper evaluates some recent developments in conceptualization with particular reference to a 'trauma amplification' model of pathological organizations that could be of assistance in formulating the treatment needs of violent offenders.